Virtual Reality as a Moderator of Psychedelic-Assisted Psychotherapy - Sekula, Agnieszka D.; Downey, Luke; Puspanathan, Prashanth (Frontiers in Psychology, 2022)
Psychotherapy with the use of psychedelic substances, including psilocybin, lysergic acid diethylamide, ketamine, and 3,4-methylenedioxymethamphetamine, has demonstrated promise in treatment of post-traumatic stress disorder, anxiety, addiction, and treatment-resistant depression. Psychedelic-assisted psychotherapy (PP) represents a unique psychopharmacological model that leverages the profound effects of the psychedelic experience. That experience is characterized by strong dependency on two key factors: participant mindset and the therapeutic environment. As such, therapeutic models that utilize psychedelics reflect the need for careful design that promotes an open, flexible, trusting mindset and a supportive setting. To meet this need, the PP model is increasingly supplemented by auxiliary methods, including meditation, relaxation, visualization or spiritual practices. We suggest virtual reality (VR) as a full-spectrum tool able to capitalize on and catalyze the innately therapeutic aspects of the psychedelic experience, such as detachment from familiar reality, alteration of self-experience, augmentation of sensory perception and induction of mystical-type experiences. This is facilitated by VR’s evidenced capacity to: aid relaxation and reduce anxiety; buffer from external stimuli; promote a mindful presence; train the mind to achieve altered states of consciousness (ASC); evoke mystical states; enhance therapeutic alliance and encourage self-efficacy. While these unique VR features appear promising, VRs potential role in PP remains speculative due to lack of empirical evidence on the combined use of VR and PP. Due to increased commercial interest in this synergy there is an urgent need to evaluate this approach. We suggest specific VR models and their role within PP protocols to inspire future direction in scientific research, and provide a list of potential disadvantages, side-effects and limitations that need to be carefully considered. These include sensory overstimulation, cyber-sickness, triggering memories of past traumatic events as well as distracting from the inner experience or strongly influencing its contents. A balanced, evidence-based approach may support transition into and out of an altered state of consciousness, provide continuity across all phases of treatment, deepen ASC experiences including mystical states and enrich the psychotherapeutic process of integration. We conclude that the potential application of VR in modulating PP demands further exploration and an evidence-based approach to both design and implementation.